A Method to Evaluate Energy Performance of Buildings Cooled by Room Air Conditioners. (August 2015) - Lucas, Franck; Ortega, Pascal; David, Mathieu; Sinama, Frantz; Brangeon, Boris; Picgirard, Fabien
Abstract: Because of their low cost, small air conditioning systems (AC) like split air conditioning systems are often installed without a proper study of building envelope performance. Furthermore, these systems are sometimes installed by tradesmen who neglect to comply with the appropriate rules and regulations. Finally, when routine maintenance is not rigorously carried out (as so often happens), the energetic performance of the system is compromised over time. This article presents a practical, global approach to diagnose the performance of existing small air-conditioning installations in buildings applied in Reunion Island. This tropical Island aspires to become electricity self-sufficient. This approach relies on a numerical tool and dynamic simulations of buildings equipped with AC. The simulations, which take account of the building envelope, a description of the system as well as the practices of the users, are based on the kernel calculation EnergyPlus. They also take into account the climatic conditions and provide an estimate of the annual electricity consumption related to the cooling of the zone. This global analysis helps to qualify the entire system by assigning an energy label. In addition to the tool, a diagnostic procedure is proposed, helping an auditor defining guidance to improve the building envelope and to install and maintain the system.